The effect mechanism of perceived entrepreneurial environment on Chinese college students’ entrepreneurial intention: chain mediation model test - Lin, Qicheng; Chen, Yirong; Lai, Junli; Zhang, Xinyi (Frontiers in Psychology, 2024)
Introduction This study aimed to explore the effect of perceived entrepreneurial environment among Chinese college students’ entrepreneurial intention and its underlying mechanism. Methods Based on a survey of 445 college students from 5 universities with the perceived entrepreneurial environment assessment scale, the achievement motivation scale, the entrepreneurial self-efficacy scale, and the entrepreneurial intention questionnaire. Results There were significant correlations among perceived entrepreneurial environment, achievement motivation, entrepreneurial self-efficacy, and entrepreneurial intention, and perceived entrepreneurial environment could significantly positively predict entrepreneurial intention. Achievement motivation and entrepreneurial self-efficacy played significant mediating roles between the perceived entrepreneurial environment and entrepreneurial intention. There were three paths that perceived entrepreneurial environment to influence entrepreneurial intention: One was the mediating role of achievement motivation; The second was the mediating role of entrepreneurial self-efficacy; The third was the chain-mediated role of both achievement motivation and entrepreneurial self-efficacy. Discussion The internal mechanism of the relationship between perceived entrepreneurial environment and entrepreneurial intention enriches the research results of entrepreneurial psychology among college students and provides a theoretical basis for training and guiding the entrepreneurship of college students.